Freedom or Prescription: The Case for Curriculum Guidance in Enterprise and Entrepreneurship Education. (December 2014) - Rae, David; Matlay, Harry; McGowan, Pauric; Penaluna, Andrew
This article reviews the development of guidance and frameworks for enterprise and entrepreneurship education (EEE) in higher education institutions with reference to the international and European contexts as well as educational development in the UK and Ireland. The arguments for and the possible limitations and disadvantages of such frameworks are discussed. There has been extensive work on EEE and on the development of competence models, for example at secondary education level. This work is critically reviewed to identify its contribution to the development of educational guidance internationally and specifically in the UK and Ireland. The paper provides a critical narrative of the development of the Quality Assurance Agency (QAA) guidance in the UK and the Higher Education Training and Awards Council (HETAC) document in Ireland by experts involved in the design process and compares the approaches proposed. While at European level there has been greater emphasis on institutional frameworks focusing on the 'entrepreneurial university', there is scope for comparison with the above educational frameworks. Feedback and observations from enterprise educators at an international level are summarized to contextualize a debate on the value, contribution, possible disadvantages and future development of such frameworks. The international interest in and adoption of related approaches have been considerable and these are assessed. The paper has implications for educational policies on EEE at national and HE institutional levels, as well as for the practices of educators in designing, validating and delivering educational awards.